PELATIHAN PEMBUATAN MODUL DIGITAL INTERAKTIF MOBILE LEARNING DENGAN CANVA DAN HEYZINE DI SMK HANDAYANI GOWATA - Indrawaty Asfah; Nurdin Noni; Lely Novia; Fitri Radhiyani; Riny Jefri (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program focused on training vocational school teachers in developing interactive digital modules based on mobile learning. It was conducted at SMK Handayani Gowata, Gowa Regency, in response to the limited use of digital media in vocational learning and teachers’ difficulties in creating engaging and mobile-accessible materials. Fifteen teachers participated in the program, which involved conceptual presentations and hands-on practice using Canva and Heyzine platforms. The evaluation showed that participants successfully produced interactive digital modules integrated with YouTube videos and QR code-based quizzes. Most participants found the training materials relevant and easy to implement. This program not only improved teachers' digital design skills but also contributed to institutional transformation toward technology-integrated teaching.